Faith and power : Religion and politics in the Middle East - Lewis, Bernard, 1916- (Oxford ; New York, NY : Oxford University Press, 2010)
"Bernard Lewis is recognized around the globe as one of the leading authorities on Islam. Hailed as "the world's foremost Islamic scholar" (Wall Street Journal ), as "a towering figure among experts on the culture and religion of the Muslim world" (Baltimore Sun ), and as "the doyen of Middle Eastern studies" (New York Times ), Lewis is nothing less than a national treasure, a trusted voice that politicians, journalists, historians, and the general public have all turned to for insight into the Middle East. Now, Lewis has brought together writings on religion and government in the Middle East, so different than in the Western world. The collection includes previously unpublished writings, English originals of articles published before only in foreign languages, and an introduction to the book by Lewis"--Provided by publisher.
License to kill : Osama bin Ladin's declaration of jihad ; Europe and Islam ; Religion and politics in Islam and Judaism ; Islam and liberal democracy ; Free at last? : the Arab world in the Twenty-first century ; Gender and the clash of civilizations ; Democracy and religion in the Middle East ; Peace and freedom in the Middle East ; Democracy, legitimacy, and succession in the Middle East ; The relevance of history : transcript, Organization of the Islamic Conference, European Union, France ; Freedom and justice in Islam ; Europe and Islam ; Freedom and justice in the modern Middle East.
Includes bibliographical references (p. xx-xxi).
Keywords: Islam -- History; Islam -- Relations; East and West; Middle East -- Religion